Factors predicting flood preparedness literacy and flood preparedness behaviors among older adults in community - Boonyaratkalin, Panisa; Chompoonud, Somjinda; Khumpheephant, Sirimol (Thai Journal of Nursing, 2023)
This descriptive research aims to find factors predicting flood preparedness literacy and flood preparedness behaviors among older adults in community. A sample of 138 older adults from 2 districts of one province in the North-Eastern Part of Thailand, was purposively selected. The research tools were Lawton Instrumental Activities of Daily Living Scale (I-IADL) in Thai, the questionnaires on flood preparedness literacy, flood preparedness behaviors and focus group discussion guideline. Data were analyzed by a stepwise multiple regression analysis and content analysis. The results are as follows. 1) Factors predicting flood preparedness literacy are age, instrumental activities of daily living, and number of underlying diseases. These three predictors accounted for 15.5%. 2) factors predicting flood preparedness behaviors are visual ability and family income. These two predictors accounted for 15%. 3) Family support, community leader and public health officials help older adults make well preparedness. However, the update information and housewares transport assistance are needed.